2015
DOI: 10.1136/bcr-2015-210196
|View full text |Cite
|
Sign up to set email alerts
|

A trimodality approach in the management of metastatic low-grade epithelioid hemangioendothelioma of the bone

Abstract: SUMMARYA 29-year-old man presented with a 2-week history of severe pain in the left foot with no preceding history of trauma. A left foot radiograph demonstrated a cortical lucency in the mid-distal shaft of the third metatarsal bone. MRI of the left foot showed an expansile lesion in the same location. A staging bone scan showed a focal uptake in the known lucency in the left third metatarsal and in the proximal left femur. A subsequent left hip radiograph demonstrated a lucency in the intertrochanteric regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…No single chemotherapy regimen has been found to be 100% successful, and the chemotherapy methods employed are based on a succession of EHEs involving many locations. In numerous documented case series, anthracyclines were the most commonly used first-line chemotherapeutic agents [24][25][26]. A series of 29 patients with multicentric or localized bone EHE was published in 1986, with a follow-up of 33 months after surgery or adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…No single chemotherapy regimen has been found to be 100% successful, and the chemotherapy methods employed are based on a succession of EHEs involving many locations. In numerous documented case series, anthracyclines were the most commonly used first-line chemotherapeutic agents [24][25][26]. A series of 29 patients with multicentric or localized bone EHE was published in 1986, with a follow-up of 33 months after surgery or adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 5 , 10 Saste et al described success in using radiation therapy in combination with chemotherapy to treat a multifocal lower extremity EHE on a young male patient. 11 Albakr et al reviewed the current literature of spinal EHE management and describes how post-operative RT with doses ranging from 40 to 60 Gy obtained local pain control and better quality of life by at least 1-year follow-up. 12 Kleer et al reported on a series of 40 cases EHE of bone, however was unable to conclude the efficacy of RT given the metastatic disease present in the majority of patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions are frequently found in bone, lung, liver, soft tissue, and skin [1] [2]. Most EHE patients are asymptomatic at the time of the diagnosis, but as the disease advances, severe burning pain is the most common symptom [3]. Currently, various therapies, including drug treatment [4] [5], interventional therapy [6], radiotherapy [7], and surgical treatment [8] have been described, however, none of these therapies can completely cure this disease, and pain may become more and more refractory [9].…”
Section: Introductionmentioning
confidence: 99%